Perennialism and Universal Reality - Irwandra, Irwandra (Institut Agama Islam Negeri Kerinci, 2022)
The universal reality actually presents two intertwined realities, mutually reinforcing and explaining, namely the esoteric and exoteric aspects. Esotericism is the essence or substance, while exotericism is the form or format of reality itself. The perspective of perennialism does not only focus on existing diversity, but also reacts to the perspectives and attitudes of human life that have begun to be enslaved and